Understanding Fencing Offenses in Indonesia: Between Legal Sanctions and Criminological Prevention - Pandapotan Damanik; Elpina; Van Lodewijk Purba; Zepa Frado Alexander Sinaga (Academic Solution Publisher, 2025)
Fencing, etymologically, derives from the word